Does Aortic Valve Replacement Surgery Improve Patients’ Quality of Life? - Coelho, Pedro (2018)
Introduction: Aortic valve replacement surgery is done to increase patients’ life expectancy and improve their health-related quality of life. Several published studies have found improvement in health-related quality of life after this procedure, but none have involved patients in Portugal. This study sought to evaluate patients’ health-related quality of life after the implantation of aortic prostheses and compare these values with preoperative health-related quality of life and the general Portuguese population’s health-related quality of life.Material and Methods: A retrospective study was done with elective patients who underwent implantation of an aortic prosthesis between August 2011 and April 2016. Health-related quality of life was evaluated using the Short Form 36 Health Survey and Short Form 6 Health Survey questionnaires in the preoperative period and 3, 6 and 12 months post-surgery. Descriptive and inferential analyses were conducted to process the data and compare preoperative health-related quality of life with postoperative values and the Portuguese population’s norms.Results: The sample included 506 patients with an average age of 70.6 years. The majority are male (53.6%). The postoperative results show a statistically significant improvement compared to preoperative health-related quality of life in all eight dimensions of the Short Form 36 Health Survey. When contrasted with the general Portuguese population, patients’ health-related quality of life is lower in the preoperative period, improving postoperatively and reaching higher than average health-related quality of life levels in some subgroups of patients and in various dimensions. An analysis of the Short Form 6 Health Survey results revealed that the patients undergoing this surgery have a higher level of preoperative problems compared with the general population, but these patients’ values approach those of the general population by the end of one year post-surgery.Discussion: This is the first study in Portugal that compares health-related quality of life using a validated scale, before and after the aortic prosthesis implantation surgery. The results demonstrate a significant improvement in all dimensions, which is not consistently observed in other published studies. Conclusion: The results confirm that the implantation of aortic prostheses improves patients’ health-related quality of life, over time bringing it close to the general population’s levels.